Within-session habituation and salivary cortisol during exposure treatment in obsessive-compulsive disorder – A link and an influence of DHEA? - Michael Kellner; Alexander Yassouridis; Christoph Muhtz; Klaus Wiedemann (Indian Journal of Psychiatry)
Background: Glucocorticoids increase fear extinction in preclinical and human studies. Endogenous cortisol might influence who will benefit from exposure therapy in anxiety-spectrum disorders. Methods: To investigate the impact of cortisol levels on within-session habituation of distress – a measure of success of exposure therapy – in obsessive-compulsive disorder (OCD) fifty-one OCD patients were studied during their stressful first cognitive-behavioral exposure therapy session with response prevention. Subjective units of distress, salivary cortisol, and salivary dehydroepiandrosterone (DHEA) were measured repeatedly before and during this afternoon session. Results: No significant association of within-session habituation of distress and cortisol level during exposure was found. Calculating with the cortisol/DHEA ratio, similar results emerged. Conclusion: Studies using endogenous diurnal fluctuation of cortisol and studies with administration of exogenous cortisol are needed to test whether glucocorticoids can augment exposure session outcome.